Picketline KZA e.a. voor de vrijlating van politieke gevangenen in Zuid-Afrika op de Dam in Amsterdam
Picketline KZA e.a. voor de vrijlating van politieke gevangenen in Zuid-Afrika op de Dam in Amsterdam.